Nature-based experience in Venetian lagoon: Effects on craving and wellbeing in addict residential inpatients - Benvegnù, Giulia; Semenzato, Mauro; Urbani, Alberto; Zanlorenzi, Isadora; Cibin, Mauro; Chiamulera, Cristiano (Frontiers in Psychology, 2024)
Introduction It is known that exposure to the natural environment may positively modulate mental processes and behaviors; in particular, it can reduce stress, anxiety, and depressive symptoms. This suggests a potential integration of “nature experience” into the treatment for substance use disorder (SUD) since various types of addiction are associated with anxiety and depression. Considering that only one study has been reported to date in patients with alcohol use disorder, the effect of nature experience in SUD patients' needs to be further investigated. This study aimed to test the effects of exposure to a natural lagoon environment on craving and measures of wellbeing in SUD patients in comparison to exposure to an urban environment. Methods Twenty-four SUD patients were divided into three groups of eight participants and exposed to two walking sessions (interspersed with a 1-week wash-out period) in a natural environment typical of the Venetian lagoon, an Urban walk, or staying at the residential center based on a Latin-square design. Before and after each session, drug craving, mood, wellbeing, agency, openness to the future, and restorativeness were assessed. Results The Nature walk significantly decreased craving in participants compared to their pre-walk values, and compared to craving after the Urban walk, with the latter significantly increased vs. pre-walk values. The Nature walk significantly decreased negative mood and increased wellbeing and agency. Openness to the future and restorativeness measures showed significant improvement after the Nature walk compared to the Urban walk. On the other hand, craving scores after the Urban Walk positively correlated with negative mood and a Sense of Negative Agency values and negatively correlated with wellbeing scores. Discussion Our results confirm that “nature experience” may improve mood, wellbeing, attention, stress relief, openness, and sense of being active in SUD patients. Moreover, we also showed a specific effect on drug craving—a key symptom of SUD.